MANAGERIAL SKILLS AND PROMOTION OF ENTREPRENEURIAL ACTIVITIES OF SILVERBIRD GROUP LIMITED IN PORT-HARCOURT (Journal of the Management Sciences, 2025)
This research work investigated how managerial expertise affects the progress of entrepreneurial endeavours within Silverbird Group Ltd, located in Port-Harcourt. The study objectives are to; determine the influence of technical skills on market research, analyze the effect of interpersonal skills on creative marketing strategies, and evaluate the role of problem-solving skills in promoting the local business of Silverbird Group Ltd in Port-Harcourt. The research employed a survey design methodology. The population is comprised of 108 managerial personnel from Silverbird Group Ltd located in Port Harcourt, Rivers State. The method employed for gathering data involved the use of questionnaires. The hypotheses were examined through the application of linear regression analysis. The study found out that technical skill has a significant positive effect on market research, interpersonal skills have significant positive effect on creative marketing strategies and problem-solving skill has a significant positive effect on promoting local business of Silverbird Group Ltd in Port Harcourt. The research findings indicate that managerial expertise plays a vital part in developing the entrepreneurial endeavours of Silverbird Group Ltd in Port Harcourt. The study proposes, among others, that the management of private organisations should periodically organise seminars and conferences that enhance the managerial skills of their staff.
Keywords: Managerial Skill; Promotion; Entrepreneurial Activities; Silverbird; Port Harcourt